The Role of Work Facilities, Employee Engagement, and Work Ethic in Enhancing Employee Performance with Job Satisfaction as an Intervening Factor at CV. Anugerah Tirta Persada Pangkalan Bun - Cipta, Hendra; Hwihanus (GoAcademica Research & Publishing, 2024)
This study explores the intricate relationships between work facilities, employee engagement, work ethic, job satisfaction, and employee performance within CV Anugrah Tirta Persada Pangkalan Bun. The research seeks to determine the impact of these factors on job satisfaction and how job satisfaction mediates their influence on employee performance. Utilizing a saturation sampling method, the study encompasses all 39 employees of the company. Data was collected via a comprehensive questionnaire covering respondent characteristics, work facility scale, work engagement scale, work ethic scale, job satisfaction scale, and employee performance scale, analyzed using SMARTPLS. Key findings reveal that work facilities and employee engagement do not significantly affect job satisfaction, as evidenced by p-values of 0.449 and 0.410, respectively. Conversely, work ethic significantly enhances job satisfaction with a p-value of 0.000. Job satisfaction is confirmed as a substantial predictor of employee performance (p-value 0.000). While job satisfaction significantly moderates the influence of employee engagement on performance (p-value 0.010), it does not moderate the effects of work facilities or work ethic on performance. Additionally, work ethic directly influences employee performance (p-value 0.012), while work facilities do not show a significant direct impact (p-value 0.177). These insights suggest prioritizing work ethic and employee engagement over work facilities to enhance job satisfaction and performance. The findings contribute valuable perspectives to human resource management practices, emphasizing the need for organizations to foster strong work ethics and employee engagement to boost overall performance.